The Impact of Corporate Social Responsibility and Financial Performance on Tax Avoidance - Kusmayadi Kusmayadi; Dewi Sri Marsanti; Didiek Susilo Tamtomo (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this study is to examine the impact of corporate social responsibility and financial performance on tax avoidance. The dependent variable in this study is tax avoidance as measured by the cash effective tax rate (CETR), using corporate social responsibility (CSR), debt ratio, return on investment, and size as independent variables. The study population is 5 tobacco/tobacco companies listed on the Indonesian Stock Exchange (IDX) from 2017 to 2021. The analytical technique used is multiple regression analysis. The results of this study show that among Indonesian tobacco/tobacco companies, the variables ROA and size affect tax avoidance, while the variables CSR and DR do not.